logo

Ask Questions, Get Answers

X
 

Find the equation of the asymptotes of the following rectangular hyperbola $xy-kx-hy=0$

Download clay6 mobile app

1 Answer

Toolbox:
  • http://clay6.com/mpaimg/2_toolbox%2021.jpg
  • For the standard rectangular hyperbola,the coordinate axes are taken to the asymptotes and the equation of the hyperbola is $xy=c^2$ .
  • If the centre is at $(h,k)$ with asymptotes parallel to the coordinate axes,the equation is $(x-h)(y-k)=c^2$
Step 1:
$xy-kx-hy=0$
The combined equation of the asymptotes differs only in the constant term.
Now $xy-kx-hy=xy-kx-hy+kh-kh$
$\Rightarrow x(y-k)-h(y-k)-kh$
$\Rightarrow (x-h)(y-k)-kh$
Therefore the equation of the rectangular hyperbola is $(x-h)(y-k)-kh=0$
$(x-h)(y-k)=kh$
Step 2:
This is of the form $(x-h)(y-k)=c^2$ and is an rectangular hyperbola with centre $(h,k)$ and asymptotes $x-h=0,y-k=0$
answered Jun 25, 2013 by sreemathi.v
 

Related questions

...